2017
DOI: 10.1210/jc.2017-01191
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Growth and Birth Anthropometrics in Metformin-Exposed Offspring Born to Mothers With PCOS

Abstract: Metformin exposure resulted in larger head size in offspring of overweight mothers, traceable already in utero. Maternal prepregnancy BMI modified the effect of metformin on offspring anthropometrics. Anthropometrics of offspring born to PCOS mothers differed from those of the reference population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 33 publications
3
35
2
Order By: Relevance
“…A randomized controlled trial in pregnant women with PCOS, comparing metformin to placebo, reported no significant difference in GDM prevalence 17.6% and 16.9%, respectively (107); however, the study could have been underpowered to detect change in GDM prevalence. Recent studies reported that the use of metformin during pregnancy in PCOS was associated with higher head circumference in the offspring at birth (108) and higher BMI and increased prevalence of overweight/ obesity at 4 years of age (109).…”
Section: Metformin During Pregnancy In Pcosmentioning
confidence: 99%
“…A randomized controlled trial in pregnant women with PCOS, comparing metformin to placebo, reported no significant difference in GDM prevalence 17.6% and 16.9%, respectively (107); however, the study could have been underpowered to detect change in GDM prevalence. Recent studies reported that the use of metformin during pregnancy in PCOS was associated with higher head circumference in the offspring at birth (108) and higher BMI and increased prevalence of overweight/ obesity at 4 years of age (109).…”
Section: Metformin During Pregnancy In Pcosmentioning
confidence: 99%
“…Neonates of the overweight or obese women in this study had significantly larger head circumference 34 , and the whole infant group weighed on average 500g more at one year of age compared to infants in the placebo group 33 . …”
Section: Effects Of Metformin Therapy Early In Pregnancymentioning
confidence: 59%
“…The study question arose from the surprising finding of significantly larger newborn head circumference in the two RCTs, the Pilot and the PregMet studies [10,13], which were reproduced in a third larger RCT, the PregMet2 study [12]. This led to the question of whether the larger head circumference in the metformin-exposed offspring translated to altered cognitive function in the offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous results of increased head circumference of metformin exposed newborns [13], and the re- SES socioeconomic status a maternal education measured on a scale 1-4 (1:10 y primary school, 2: high school, 3: less than 4 years of higher education, 4: 4 or more years of higher education) b paternal education measured on a scale 1-4 (1: 10 y primary school, 2: high school, 3: 3 years of higher education, 4: 5 or more years of higher education) c: scale 1-5, 1 = prepubertal, 5 = adult size genitals and breast, adult pubic hair growth [29,30], we would have expected an opposite result. However, the total prevalence of individuals with FIQ < 85 in the study population, does not exceed the expected number based on an assumption of normal distribution of IQ scores.…”
Section: Mean (Sd) Mean (Sd)mentioning
confidence: 99%
See 1 more Smart Citation